The Work of a Skilly Criticist and Scientist Oybek - Guli Tursunpulatova (Zien Journals, 2021)
This article provides information about the life and work of the great scientist, writer, Oybek. There is also detailed information about the analysis of Oybek's work.
Keywords: Fiction; poetry; prose; creativity; analysis